CRISPR-Cas9–Knockout of PD-L1 Gene in Triple-Negative Breast Cancer - Ashwaq MS Al-Jbouri; Asmaa Sami Jawad; Zainab Adil Ghani Chabuck; Saad Mardi Muhammad (Journal of Biomedicine and Biochemistry, 2025)
Triple-negative breast cancer (TNBC) remains a challenging malignancy due to its immunosuppressive microenvironment. Here, we employed CRISPR-Cas9 to knockout PD-L1 in TNBC cell lines and evaluated changes in immune recognition and T cell activation. PD-L1 ablation resulted in increased expression of antigen-presenting machinery and enhanced sensitivity to T cell-mediated cytotoxicity. Our findings suggest that CRISPR-mediated PD-L1 disruption could potentiate immunotherapy efficacy in TNBC.